Redesigning Course Placement in Service of Guided Pathways - Ross Markle (Educational Considerations, 2025)
Prior to the Guided Pathways movement, a litany of research in community colleges showed that course placement was inaccurate and ineffective. This article argues that placement might be redesigned, addressing erroneous assumptions about student success in service of pathways. This new placement would integrate three main areas of student success research, positioning placement as (1) a means of connecting with students and building sense of belonging, (2) guided by a holistic understanding of student potential, and (3) seeking to connect them with a network of effective interventions.
Keywords: Community College; Course Placement; Student Success; Holistic Support; Guided Pathways